Strategi Terpadu Penanganan Dampak Migrasi dan Penanggulangan Kemiskinan di Desa Makamenggit dan Pambotanjara, Kabupaten Sumba Timur - Manu Mesa, Asinkritus; Bustomi, Thomas; Nursalam (Jurnal Bina Praja, 2024)
Migration activities carried out by people in Makamenggit Village and Pambotanjara Village have positive and negative impacts on migrant workers, their families and communities surround. Various handling efforts carried out by the government so far are still limited to efforts to deal with problems related to migration activities namely the threat of human trafficking and facilitating Indonesian Migrant Workers (PMI) who experience problems in the workplace. Whereas, the handling efforts should reach the root of the problem, namely poverty. Therefore in this research, researchers tried to identify the impacts of migration in those villages, which is then continued with efforts to deal overcome the impacts by determining strategies through SOAR Analysis which is expected to become policy recommendations for the government or stakeholders. Researchers used descriptive qualitative method to obtain the necessary data regarding the impacts and strategies required. Result of data analysis found that migration had positive impacts namely fulfilling children's educational and health needs through remittances obtained, fulfilling household consumption needs and increasing the ability of migrant workers and their families to be involved in cultural and social affairs. Meanwhile the negative impacts namely the potential for repeated migration and hereditary migration, negative stigma towards female migrant workers and the neglection of migrant worker’s children. To overcome the various impacts of migration as well as the efforts in reducing poverty, then the integrated strategies are required which is based on empowerment efforts toward various community groups and utilization of available local potentials, both natural and human resource.